Analisis kemampuan literasi numerasi dengan konten aljabar dan bilangan siswa kelas VIII - Chairunisa, Kamila; Su'aida, Atina Himma; Arofa, Arofa; Karimah, Sayyidatul (Universitas PGRI Semarang, 2025)
Minimum Competency Assessment (MCA) is an assessment of competencies such as reading literacy and numeracy. Basically, literacy in Indonesia is low due to the lack of interest in reading and the numeracy level of Indonesian students is still at the bottom of the rankings. The purpose of this study is to describe the level of students' numeracy literacy skills and identify obstacles and aspects of abilities that need to be improved, with sampling at SMP Negeri 2 Pekalongan in the 2024/2025 school year using descriptive qualitative research methods. The research subjects consisted of 25 students who were given tests related to numeracy literacy with algebra and number content. Based on the test results, 8 students were categorized as high, 7 students as medium, 9 students as low and 1 student as very low. From the test results, 4 students were selected to take part in the interview from each category. Students in the high and medium categories were able to explain the essence of a reading and the problem solving process in the problem. While students in the low and very low categories were not able to. To improve students' ability in numeracy literacy test, teachers are advised to provide many practice problems equivalent to AKM with algebra and number content as well as literacy activities in learning.